ANALISIS PENGUKURAN KINERJA SUPPLY CHAINMANAGEMENT DENGAN METODE SUPPLY CHAINOPERATION REFERENCE (SCOR) DAN ANALYTICALHIERARCHY PROCESS (AHP) PADA INDUSTRIGARMEN DI PT XYZ - Brigitta Olivia Liestanto Putri (2023)
PT XYZ is a garment company operating in Indonesia. Previously, this company had never conducted supply chain performance measurements, which resulted in frequent problems occurring in the planning, procurement, production, and delivery processes. Therefore, it is necessary to evaluate supply chain performance to determine supply chain performance using the Supply Chain Operations Reference (SCOR) method. Measurements were carried out through several stages, namely the identification of the SCOR matrix, verification of Key Performance Indicators (KPI), weighting using the Analytical Hierarchy Process (AHP) method, and calculating normalized values. Based on the results of the study, the supply chain flow performance value obtained was 54,86 in the average category. Several performance indicators that need to be improved are the accuracy of raw material requirements planning, the ability of suppliers to meet raw material requests, the number of defective products, product quality after the delivery process, and the number of complaints from consumers. Making improvements to these indicators, it is expected to help improve supply chain performance in the company.